Does race predict short-term mortality after carotid surgery? The results of a meta-analysis. - Kennedy, Byron S. (National Medical Association, 2002)
Although African Americans are more likely to have an ischemic stroke and suffer a greater burden of stroke-related mortality and disability, they are less likely to have carotid surgery treatment than whites, even after accounting for clinical characteristics and ability to pay. Not surprisingly, little is known about their short- and long-term outcomes, including death, after undergoing carotid endarterectomy (CEA). The purpose of this study was to systematically review the published literature to clarify what role race has with respect to perioperative mortality risk following CEA. A search of MEDLINE (1966-May 2000), Scientific Citations (1945-May 2000), and the Cochrane Collaboration Stroke Group databases was performed to identify studies that related to African American-white differences for CEA mortality. Three studies met the specified eligibility criteria that allowed for the inclusion of 224,554 subjects (5,569 African Americans and 218,985 whites). Each showed some indication of increasing perioperative mortality risk for African Americans, but the findings were only significant for the studies of Hsia and colleagues (odds ratio (OR), 1.365; 95% confidence interval (CI), 1.164-1.600) and Huber and coworkers(28) (OR, 2.247; 95% Cl, 1.367-3.695) but not for the study of Estes and colleagues (OR, 1.429; 95% Cl, 0.827-2.469). After pooling the data, using a fixed-effects model, the OR was 1.429 (95% CI, 1.235-1.654). There was no evidence of significant heterogeneity between the studies and the random-effects model gave comparable results. African Americans, as compared to whites, appear to have a greater likelihood of short-term death following carotid surgery by more than 40%. This excess risk is possibly related to coexisting illness, which needs to be carefully weighed when considering a patient for CEA. Prospective studies are needed to further clarify these observed differences.